The hypocretin–orexin system regulates cocaine self-administration via actions on the mesolimbic dopamine system - España, Rodrigo A. (2009)
Recent evidence suggests that the hypocretin–orexin system participates in the regulation of reinforcement processes. The current studies examined the extent to which hypocretin neurotransmission regulates behavioral and neurochemical responses to cocaine, and behavioral responses to food reinforcement. These studies used a combination of fixed ratio, discrete trials, progressive ratio and threshold self-administration procedures to assess whether the hypocretin 1 receptor antagonist, SB-334867, reduces cocaine self-administration in rats. Progressive ratio sucrose self-administration procedures were also used to assess the extent to which SB-334867 reduces responding to a natural reinforcer in food-restricted and food-sated rats. Additionally, these studies used microdialysis and in vivo voltammetry in rats to examine whether SB-334867 attenuates the effects of cocaine on dopamine signaling within the nucleus accumbens core. Furthermore, in vitro voltammetry was used to examine whether hypocretin knockout mice display attenuated dopamine responses to cocaine. Results indicate that when SB-334867 was administered peripherally or within the ventral tegmental area, it reduced the motivation to self-administer cocaine and attenuated cocaine-induced enhancement of dopamine signaling. SB-334867 also reduced the motivation to self-administer sucrose in food-sated but not food-restricted rats. Finally, hypocretin knockout mice displayed altered baseline dopamine signaling and reduced dopamine responses to cocaine. Combined, these studies suggest that hypocretin neurotransmission participates in reinforcement processes, likely through modulation of the mesolimbic dopamine system. Additionally, the current observations suggest that the hypocretin system may provide a target for pharmacotherapies to treat cocaine addiction.